Correction: Impact of COVID-19 vaccination on mortality after acute myocardial infarction. - Mohit D Gupta; Shekhar Kunal; Girish M P; Dixit Goyal; Rajeev Kumar Malhotra; Prashant Mishra; Mansavi Shukla; Aarti Gupta; Vanshika Kohli; Nitya Bundela; Vishal Batra; Ankit Bansal; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0291090.].